2008
DOI: 10.1007/s12275-008-0011-8
|View full text |Cite
|
Sign up to set email alerts
|

Description of Streptomyces neopeptinius sp. nov., an actinobacterium with broad spectrum antifungal activities

Abstract: A streptomycete strain producing broad-spectrum antifungal substances was taxonomically characterized. The strain, designated KNF 2047(T) (= SH-09(T) = KCTC 10586BP(T)), was found to form extensively branching aerial and substrate mycelia, and produce spiny-ornamented spores with loose spiral chains. The whole cell hydrolyzates contained major amount of LL-diaminopimelic acid. The major fatty acids of the phospholipids were saturated and branched fatty acids containing 14~17 carbons, and the major isoprenoid q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Of the 19 DAB species that were obtained in this study, only three functioned as DAB against previously reported fungal pathogens and plant‐parasitic nematodes, including B. cereus , P. putida and S. flavofungini . Additionally, four species ( B. tequilensis , S. marcescens , S. albidoflavus and S. neopeptinius ) produced antifungal compounds, whereas the other four species ( B. drentensis , S. marcescens subsp. sakuensis , B. diminuta and S. alboflavus ) exhibited nematicidal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 19 DAB species that were obtained in this study, only three functioned as DAB against previously reported fungal pathogens and plant‐parasitic nematodes, including B. cereus , P. putida and S. flavofungini . Additionally, four species ( B. tequilensis , S. marcescens , S. albidoflavus and S. neopeptinius ) produced antifungal compounds, whereas the other four species ( B. drentensis , S. marcescens subsp. sakuensis , B. diminuta and S. alboflavus ) exhibited nematicidal activity.…”
Section: Discussionmentioning
confidence: 99%
“…134 Neopeptins A and B also displayed potent therapeutic ability and protective activity against powdery mildew disease. 135,136…”
Section: Identification and Biosynthesis Of Lipopeptides From Strepto...mentioning
confidence: 99%
“…The growth of Glomerella cingulata , P. oryzae , Cochliobolus miyabeanus, and Colletotrichum lagenaium can be completely inhibited by neopeptins at a concentration of 4 μg/ml. In one study, the development of powdery mildew on cucumber plants was effectively controlled by a mixture of neopeptins isolated from a culture of Streptomyces neopeptinius (Han et al, 2008; Kim et al, 2007). The tyrocidines (Fig.…”
Section: Natural Cyclic Peptides As a Disruptor Of Structural Integrimentioning
confidence: 99%